Pneumococcal vaccination in adult people living with HIV on suppressive antiretroviral therapy: a case–control study. (February 2020) - Vivancos-Gallego, MJ; Muriel, Alfonso; Serrano-Villar, Sergio; Moreno-Zamora, Ana; Pérez-Elías, MJ; Quereda, Carmen; Casado, JL; Sánchez-Conde, Matilde; Del Campo, Santos; Dronda, Fernando; Sánchez-Díaz, Ana M; Valencia-Martín, Jose Lorenzo; et al.
There is little information on the effectiveness of the pneumococcal vaccines (PVs), especially for the pneumococcal conjugate vaccines (PCVs), in HIV-infected patients in the modern antiretroviral era. This is a case–control study where cases were people living with HIV (PLWH) with confirmed pneumococcal infection (CPI) and controls were PLWH without CPI matched with cases by gender and year of HIV diagnosis. The selection process was blinded to the study factor (vaccination). Sample size estimation yielded 61 cases and 183 controls. We analyzed the effect of PV on CPI using Cox proportional-hazards regression model with time-dependent covariates. We included 256 subjects: 64 cases, and 192 controls. PVs had been administered to 115 (45%) patients. Only the modified Charlson Comorbidity Index (HR 1.16, 95%CI 1.06–1.27, P  = 0.001) and the CD4 nadir (HR 0.99, 95% CI 0.98–0.99, P  = 0.001) were independently associated with CPI. Receipt of PV was not associated with CPI after adjusting in the multivariate model with time protection as a dependent covariate (HR 0.65, 95% CI 0.35–1.32 P  = 0.250). We also investigated the influence of different immunization schedules. In an adjusted model, we found no evidence of protection against CPI, including double immunization schedules (HR 0.42 95%CI 0.15–1.19 P  = 0.102). In this case–control study, we could not show an association between pneumococcal vaccination and confirmed pneumococcal infection, although a protective effect of particular schedules of immunization cannot be ruled out.